A brief review on perovskite multiferroics. (25th January 2017) - Liu, Hongbo; Yang, Xue
ABSTRACT: The paper first introduces the basic physics behind perovskite multiferroics. Then the recent progress on simple, complex perovskites, and manganites are briefly reviewed. The review discloses two important directions on achievement multiferrocity in perovskite: pay with strain engineering and adjust octahedral deformation. The authors also suggest that specific issues like leakage current and characterization platforms are also very important for the study of multiferroics.